In vitro Effect of Recombinant Feline Interferon-Ω (rFeIFN-Ω) on the Primary CanineTransmissible Venereal Tumor Culture - Setthawongsin, Chanokchon; Tangkawattana, Sirikachorn; Rungsipipat, Anudep; Techangamsuwan, Somporn (Frontiers in Veterinary Science, 2019)
Background: Interferons (IFNs), signaling proteins produced by host cells, are secreted in response to pathogen activity as well as to tumor cells, and display antiviral, antiproliferative and immunomodulatory effects. Recombinant feline interferon omega (rFeIFN-ω) has in vitro growth inhibition activities on various canine and feline tumor cell lines. Canine transmissible venereal tumor (CTVT) is used as an animal model for immunotherapy due to its specific growth phase. Previous studies have usually focused on the interaction between tumor infiltrating lymphocytes and CTVT cells. However, the specific effects of rFeIFN-ω on CTVT cells remains poorly defined. Aims: The aims of this study, therefore, were to evaluate the in vitro effect of rFeIFN-ω on primary CTVT cells and to study the mRNA expression of apoptotic genes and drug resistance genes. Materials and Methods: Purified CTVT cells were treated with various concentrations of rFeIFN-ω and the viability of the cultured cells was ascertained at 24, 48 and 72 h post treatment (hpt) and a dose-response curve plotted. The transcriptome analysis of apoptotic (Bax and Bcl-2) and drug resistance (ABCB1 and ABCG2) genes was performed by reverse transcription quantitative real-time PCR at 72 hpt. Results: rFeIFN-ω displayed an antiproliferative activity against CTVT cells in a dose-dependent manner within 72 hpt. The relative mRNA expression of Bcl-2 was upregulated only at a rFeIFN-ω concentration of 104 IU/100 µl. However, higher concentrations of rFeIFN-ω gave a higher level of relative mRNA expression of both ABC transporter genes. Conclusion: This study provided the information of in vitro effect of rFeIFN-ω on CTVT cells in a dose dependent manner. These results encourage future in vivo studies to evaluate the potential efficacy of this treatment.